1992
DOI: 10.1002/lsm.1900120511
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast imaging of tissue ablation by a XeCl excimer laser in saline

Abstract: To determine the temporal evolution of laser induced tissue ablation, arterial wall specimens with either hard calcified or fatty plaques and normal tissue were irradiated in a 0.9% saline solution using a XeCl excimer laser (wavelength 308 nm, energy fluence 7 J/cm2, pulse width 30 ns) through a 600 microns fused silica fiber pointing perpendicular either at a 0.5 mm distance or in direct contact to the vascular surface. Radiation of a pulsed dye laser (wavelength 580 nm) was used to illuminate the tissue sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In contrast to earlier observations, in vitro [9][10][11][12] and in vivo [13,14] studies have demonstrated the explosive nature of tissue ablation by excimer laser pulses: Each ablative laser pulse absorbed by tissue or by blood will induce a rapidly expanding and imploding water vapor bubble (lifetime up to 300 s, diameter up to 3 mm) and stress waves. We demonstrated that within tissue, the explosive water vapor bubble expansion separates tissue layers [13].…”
Section: Introductionmentioning
confidence: 70%
“…In contrast to earlier observations, in vitro [9][10][11][12] and in vivo [13,14] studies have demonstrated the explosive nature of tissue ablation by excimer laser pulses: Each ablative laser pulse absorbed by tissue or by blood will induce a rapidly expanding and imploding water vapor bubble (lifetime up to 300 s, diameter up to 3 mm) and stress waves. We demonstrated that within tissue, the explosive water vapor bubble expansion separates tissue layers [13].…”
Section: Introductionmentioning
confidence: 70%
“…Further refinement probably should be directed at ensuring work. Previous investigators have suggested that pressure transients might be due to volume expansion and/or implosion of cavitation bubbles, to hypersonic shock waves, or to microplasma formation [19,20]. The physical basis for potentially detrimental effects, strong absorption of 308-nm radiation by blood, plaque, and contrast, with consequent conversion of radiation into the energy of vaporization, is well documented [2 1-24].…”
Section: Discussionmentioning
confidence: 99%
“…Photoacoustic waves and probe contact pressure assist tissue ablation [3,7,241 by providing additional energy for bond dissociation and debris removal. Generation of bubbles and subsequent shock waves have been shown to occur at energy densities below the water vaporization threshold [31, thereby lysing cell membranes [lo] and producing explosive ejection of ablated tissue [25]. Whereas it is possible for ablation products to be trapped between the tissue and probe in certain laser procedures, the high level of tissue hydration inherent with ab interno sclerostomy procedures and the easy deformity of soft ocular tissue prevent such entrapment of ablation debris.…”
Section: Composite Ablation Mechanismmentioning
confidence: 99%